Economics and politics of energy in the Middle East and Eastern Europe - Ketenci, Natalya Shevchik; Sevencan, Ayşe; Altınanahtar, Alper; Ketenci, Natalya; Levent Uslu, Çağrı; Çakmak Alioğlu, Gizem; Güner, Melih; Baykan, Barış Gencer; Vural, Gülfer (Lexington Books, 2021)
The contributors to this volume analyze the complex interconnectivity between the Middle East and Eastern Europe through the economics and politics of energy. Individual chapters explore the shift from non-renewable to renewable energy sources, the influence of energy policy on political alliances, and the future of energy policy in the region.